Night time smoking among Bangladeshi adults: effect on sleep quality and musculoskeletal health (Asian Journal of Medical and Biological Research, 2022)
Quality of sleep is linked to a number of illnesses, including cardiovascular problems, diabetes, mental and behavioral issues. The study determined the impact of night time smoking on sleep quality and musculoskeletal health. A cross -sectional study was conducted among desk-based officials of Dhaka city between June to September 2022 using convenient sampling technique. Sleep quality was measured by Pittsburgh Sleep Quality Index (PSQI). Data were collected through structured interview and analyzed by IBM SPSS 25 statistical package software. A total of 261 desk-based officials who do smoke were included in this study and among them, 132 (50.6%) were night time smokers. More than half of the study participants had poor sleep quality (58.6%). Night time smoking habit (OR= 2.59, 95% CI: 1.55 - 4.32) and doing a job in a private organization (OR=1.71, 95% CI: 1.02 - 2.85) were a significant predictor of poor sleep quality. On the other hand, various musculoskeletal health issues such as pain in the shoulder/ neck, pain in the back/ lower back, and pain in arms etc. were also scientifically associated with night time smoking habit (P